STRUGGLE FOR SPACE IN COASTAL CITIES: A CELLULAR AUTOMATA MODEL FOR SIMULATING URBAN STRATIFICATION DYNAMICS - Feitosa, Flavia da Fonseca; Maretto, Raian Vargas; Monteiro, Antônio Miguel Vieira (Revista Brasileira de Cartografia, 2018)
The social production of Brazilian cities has historically accentuated the diï¬€erences between urban locations and promoted urban stratification. This reality is particularly pronounced in coastal areas, where the locational advantages of areas near the sea create an increasingly competitive and exclusionary land market. Through methods of computational modeling and simulation, this work analyzes the production of the urban space of Caraguatatuba, a Brazilian city located on the northern coast of São Paulo State. We developed a cellular automata model called URBIS-Caragua to explore the dynamics of urban stratification bounded by urban legislation and the spatial distribution of residential location opportunities. In this process, particular attention was directed towards the empirical parameterization of the model, which relied on exploratory data analysis and statistical models for the periods 1991-2000 and 2000-2010. Through the parameterization and development of simulation experiments about past dynamics, it was possible to obtain new insights about how trends of urban expansion and stratification changed over the recent years, and the possible relation of these trends to urban legislation, locational factors and sociodemographic pressures. The experiments about future dynamics (2010-2025) indicated that the Master Plan of the city, approved in 2011, is likely to reinforce trends that have historically established an unequal distribution of opportunities for residents that belong to diï¬€erent social groups.